Fulfillment Of Women's Rights In Prisons - Mitro Subroto; Heruda Ortega Sinurat (Universitas Merdeka Madiun, 2025)
Abstract Introduction to the Problem: Women in correctional institutions have specific needs that must be met, particularly regarding the right to health, protection from violence, and rehabilitation and social reintegration programs. However, in practice, the fulfillment of these rights is often not optimal due to various challenges, including limited facilities, the lack of gender-sensitive policies, and rehabilitation programs that do not adequately address their needs. Purpose/Study Objectives: This study aims to analyze the extent to which women's rights are fulfilled in correctional institutions, focusing on three main aspects: the right to health, protection from violence, and rehabilitation and social reintegration programs. Design/Methodology/Approach: This research employs a qualitative approach using interviews, observations, and documentation methods. Data is collected through interviews with female inmates and correctional officers, direct observation of prison conditions, and an analysis of relevant policies and regulations. Findings: The findings indicate that the fulfillment of women's health rights in correctional institutions is still not optimal, particularly in reproductive health, due to limited health facilities and services. Additionally, protection from physical and psychological violence is inadequate due to a lack of gender-sensitive supervision and training for officers. The available rehabilitation programs are also considered irrelevant to the specific needs of female inmates, especially in preparing them for reintegration into society after serving their sentences. Therefore, improvements in health facilities, gender-sensitive officer training, and more inclusive rehabilitation programs for female inmates are necessary. Paper Type: Research Article